2006
DOI: 10.1080/02841860500486630
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, pattern and timing of brain metastases among patients with advanced breast cancer treated with trastuzumab

Abstract: (2006) Incidence, pattern and timing of brain metastases among patients with advanced breast cancer treated with trastuzumab, Acta Oncologica, 45:2,[196][197][198][199][200][201]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 21 publications
3
78
0
3
Order By: Relevance
“…Cumulative 3-year risk of brain relapse of 42% is in the range found in other series of HER2-positive advanced breast cancer patients [11][12][13][14][15][16][17]23]. In this cohort the average annual risk of symptomatic brain relapse for surviving patients during consecutive 7 years of follow-up was 10%, with no apparent plateau.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Cumulative 3-year risk of brain relapse of 42% is in the range found in other series of HER2-positive advanced breast cancer patients [11][12][13][14][15][16][17]23]. In this cohort the average annual risk of symptomatic brain relapse for surviving patients during consecutive 7 years of follow-up was 10%, with no apparent plateau.…”
Section: Discussionsupporting
confidence: 68%
“…The knowledge on the predictive value of steroid receptor status for brain metastases in HER2-positive advanced breast cancer patients is scarce. A recent study including patients administered trastuzumab did not demonstrate any association between ER status and the risk of brain relapse [17]. Pathological tumor grade in general breast cancer population is considered highly predictive for clinical behavior of breast cancer, including the risk of brain relapse [18]; however, the impact of this feature in HER2-positive patients is also not well recognized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Vuong et al [196] found males had a higher prevalence of brain metastasis than females (p<0.001), but the frequency of brain metastasis in a study conducted by Pickren et al [131] was not different (8.8% in men and 8.7% in women). Race has not been associated with brain metastasis [131] and was not included as a covariate in the majority of studies [8,9,185,187,[189][190][191][192][193][194][195][197][198][199][200][201][202][203][204]. Breast cancer is the most common source of brain metastasis for women [5].…”
Section: Risk Factorsmentioning
confidence: 99%